The Effect of Using Endorphin Massage for Decreasing Pain at First Stage in Normal Labor - Astuti, Siti Choirul Dwi; Sari, Riana Trinovita (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2022)
Labor pain is a subjective experience of physical sensations associated with uterine contractions, dilation, thinning cervix and fetal descent during labor. To resolve the pain of labor, it has been implemented in a nonpharmacological method which is endorphin massage, in understanding endorphin massage for pressing pain in the first stage, in an active phase of normal multiparous mothers' deliveries. This research aims to research endorphin massage's influence on suppressing pain during the active phase of normal labor of multiparous mothers. This study is quasi-experimental with a cross-sectional approach. The study population of all women giving birth administered the purposive sampling data capture techniques, and it was obtained 132 multiparous mothers with normal labor in the observation sheet. Data were examined by administering a T-test. The majority of the pain intensity in the first stage of active phase multiparous mothers with normal labor, before the breath relaxation, is severe, with up to 49% experiencing severe pain. The majority of the percentage of moderate pain in the first stage of active phase multiparous mothers with normal labor, after breath relaxation, is as high as 42%. Meanwhile, the pain intensity of the first stage in active phase multiparous mothers with normal labor, prior to endorphin massage, is as high as 73.3%. Pain intensity of the first stage in active phase multiparous mothers normal labor after endorphin massage, the majority of the percentage is moderate pain up to 53.3%. Statistical test results obtained p-value is 0.004 endorphin massage. In conclusion, there is an effect of breath relaxation on the intensity of pain during normal labor in multiparous mothers. Furthermore, researchers can do a combination of endorpine massage with other treatments to treat pain during the I active phase of labor and pain intensity checks can be done by testing cortisol levels.